2021
DOI: 10.5194/hess-2021-263
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Towards Effective Drought Monitoring in the Middle East and North Africa (MENA) Region: Implications from Assimilating Leaf Area Index and Soil Moisture into the Noah-MP Land Surface Model for Morocco

Abstract: Abstract. The Middle East and North Africa (MENA) region has experienced more frequent and severe drought events in recent decades, leading to increasingly pressing concerns over already strained food and water security. An effective drought monitoring and early warning system is thus critical to support risk mitigation and management by countries in the region. Here we investigate the potential for assimilation of leaf area index (LAI) and soil moisture observations to improve representation of the overall hy… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…Our findings also showed how the Sentinel-1 γ 0 VV DA has a larger impact on the temporal dynamics of irrigation, whereas the VH polarization has a stronger influence in adjusting the bias, and one potential reason could be the high sensitivity of the vegetation to root-zone soil moisture and vice versa (Modanesi et al, 2021). Similar conclusions were obtained by Nie et al (2022) over Morocco. This recent study showed how the assimilation of MODIS LAI into Noah-MP v.4.0.1, with and without activating irrigation, provides critical information to improve the root-zone soil moisture and more generally water-energy-carbon fluxes.…”
Section: Data Assimilationsupporting
confidence: 82%
“…Our findings also showed how the Sentinel-1 γ 0 VV DA has a larger impact on the temporal dynamics of irrigation, whereas the VH polarization has a stronger influence in adjusting the bias, and one potential reason could be the high sensitivity of the vegetation to root-zone soil moisture and vice versa (Modanesi et al, 2021). Similar conclusions were obtained by Nie et al (2022) over Morocco. This recent study showed how the assimilation of MODIS LAI into Noah-MP v.4.0.1, with and without activating irrigation, provides critical information to improve the root-zone soil moisture and more generally water-energy-carbon fluxes.…”
Section: Data Assimilationsupporting
confidence: 82%
“…Therefore, irrigation is essential in the MENA region to sustain agricultural yield, land productivity, farmers' profit, and AVA. Irrigation is also a response to the growing worries about food and water securities, which are already strained (Nie et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…We used the dynamic phenology model within Noah-MP to account for plant processes that respond to cold, heat, and drought stresses 32 . The model simulates leaf area index due to senescence or herbivory.…”
Section: Methods and Data For CDI Productionmentioning
confidence: 99%